2000
DOI: 10.1046/j.1365-2184.2000.00183.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased cellular hypoxia and reduced proliferation of both normal and leukaemic cells during progression of acute myeloid leukaemia in rats

Abstract: The microenvironmental changes in the bone marrow, spleen and liver during progression of the transplantable promyelocytic leukaemia in the Brown Norwegian rat (BNML) have been studied. We used flow cytometry to estimate cellular hypoxia and proliferation based on in vivo pulse-labelling with a mixture of 2-nitroimidazole linked to theophylline (NITP) and bromodeoxyuridine (BrdUrd). The leukaemic cells were identified with the RM124 antibody. In rats inoculated with leukaemic cells the fraction of RM124+ cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 14 publications
0
54
0
Order By: Relevance
“…Prominent examples include differentiation induction therapy, developed from preliminary studies with cyclic adenosine monophosphate (cAMP) inducing cholera toxin in the BNML and BNML-cholera toxin-resistant models, 161,268 269 circuitously leading to the clinical studies of agents such as theophylline 273 (cAMP induction/stabilisation), Gemtuzumab ozogamicin 274 (conjugated mAb) and granulocyte colony-stimulating factor 275 (G-CSF-cytokine). These results and the application of the BNML rat model in more recent work pertaining to angiogenesis and microenvironmental modifications by Iversen et al [276][277][278][279] rationalise continued interest in this model.…”
Section: Mrd Detection and Treatment In Bnmlmentioning
confidence: 77%
“…Prominent examples include differentiation induction therapy, developed from preliminary studies with cyclic adenosine monophosphate (cAMP) inducing cholera toxin in the BNML and BNML-cholera toxin-resistant models, 161,268 269 circuitously leading to the clinical studies of agents such as theophylline 273 (cAMP induction/stabilisation), Gemtuzumab ozogamicin 274 (conjugated mAb) and granulocyte colony-stimulating factor 275 (G-CSF-cytokine). These results and the application of the BNML rat model in more recent work pertaining to angiogenesis and microenvironmental modifications by Iversen et al [276][277][278][279] rationalise continued interest in this model.…”
Section: Mrd Detection and Treatment In Bnmlmentioning
confidence: 77%
“…The lack of oxygen in BM is possibly further aggravated with anemia that often accompanies newly diagnosed AML patients. In fact, Jensen et al 15 have reported that hypoxic fraction of leukemic cells and normal cells inoculated in the Brown Norwegian rat increase significantly in the BM. On the other hand, leukemic cells are cultured in vitro at ambient oxygen (21%) in most circumstances, while in vivo cells are physiologically exposed under much lower oxygen levels ranging from 16% in pulmonary alveoli to less than 6% in most peripheral organs of the body.…”
Section: Introductionmentioning
confidence: 99%
“…Although these concepts have been developed for solid tumors, oxygen levels also may be particularly low around leukemia cells. Indeed, bone marrow, which is physiologically characterized by a high level of cell crowding and poor vascularization [1], can undergo a further reduction of oxygenation in patients with leukemia [10] as a result of the fast growth of leukemia cells and anemia, which commonly develops as a consequence of leukemic growth.…”
Section: Introductionmentioning
confidence: 99%